Pengaruh Latihan Sandbag Dan Latihan Sepeda Statis Terhadap Aktifitas Fungsional Penderita Osteoarthritis Lutut - Karman, Wa Ode Suci Candrawati, Agus Widodo, S.Fis, M.Kes (2016)
Backgound : Osteoarthritis (OA) is a degenerative disease in which the joint cartilage are found. The main complaint on osteoarthritis is pain, especially in the medial part of the knee, so that may have limited movement, and limitation in performing functional activities. Sandbag exercise and static bike exercise can solve the problem in this case thus increasing the functional activity of the patient. The aim of research : to determine the effect of differents in sandbag exercise and a static bike exercise on the activites of functional knee osteoarthritis. Method of research : Using a quasi-experimental with two group pre and post test design. Samples at 20 responder patients with osteoarthritis of the knee at the Dustira Hospital in Cimahi. Respondents were divided into two different treatment, first treatment with 10 respondents are given a sandbag xercise, while the second treatment with the 10 people are given a static bike exercise. Analysis of data using Willcoxon Test and Mann Whitnney Test. Result of research: First treatment with a sandbag exercise is obtained value of p = 0.005 and second treatment with a stationary bicycle exercise is obtained value of p = 0.005. Based on different test the influence of sandbag exercise and a static bike exercise is obtained value of 0.130. Conclusion : There is the influence of sandbag exercise and a static bike exercise on the functional activities of knee osteoarthritis patients. There is no significant difference between the sandbag exercise and a static bike exercise on the functional activities of knee osteoarthritis patients.